Technical efficiencies of faculties of economics in Turkey - ÇOKGEZEN, MURAT (My University, 2009)
This is the first study of technical efficiencies of higher education institutions and the first study evaluating performance at faculty level in Turkey. The study also compares technical efficiencies of private and public institutions. Estimation shows low overall efficiency with high variations across the faculties of economics. The results also demonstrate that average efficiency of public institutions is higher if the quality of data is not considered. However, when qualities of the outputs are taken into account, average efficiencies of public and private institutions converge.
Keywords: Data envelopment analysis; Faculty of economics; Higher education; Technical efficiency